DDX3X mutations in two girls with a phenotype overlapping Toriello-Carey syndrome - Dikow, Nicola; Granzow, Martin; Karch, Stephanie; Hinderhofer, Katrin; Paramasivam, Nagarajan; Kaufmann, Lilian; Fischer, Christine; Evers, Christina; Eils, Roland; Bartram, Claus R.; Moog, Ute (American journal of medical genetics, 2017)
Recently, de novo heterozygous variants in DDX3X have been reported in about 1.5% of 2659 females with previously unexplained intellectual disability (ID). We report on the identification of DDX3X variants in two unrelated girls with clinical features of Toriello-Carey Syndrome (T-CS). In patient 1, the recurrent variant c.1703C>T; p.(P568L) was identified when reconsidering X-linked de novo heterozygous variants in exome sequencing data. In patient 2, the DDX3X variant c.1600C>G; p.(R534G) was also detected by exome sequencing. Based on these data, de novo heterozygous DDX3X variants should be considered not only in females with unexplained ID, but also in individuals with a clinical diagnosis of T-CS.